PENGARUH KESEHATAN DAN KESELAMATAN KERJA TERHADAP KINERJA KARYAWAN PADA PT. FRASTA SURVEY INDONESIA DI SITE KALIMANTAN - Wibowo, Sugeng; Slamet, Giarti (Surakarta Management Journal, 2021)
This study aims to identify how much influence the health and safety of employees so that it affects employee performance. This research was conducted at PT. Frasta Survey Indonesia or more specifically Singa Gembara Village, North Sangatta District, Kutai Kartanegara Regency, East Kalimantan Province, and this research was carried out in June 2021. The sampling in this study used 55 respondents, the data collection technique was through a distributed questionnaire. to respondents, and the research variables are Health (X1), Safety (X2), Performance (Y). This study uses descriptive analysis with a quantitative approach, and to test the level of reliability using Cronbach Alpha and then the data is processed by Multiple Linear Regression Analysis. Hypothesis testing using the F test and t test with a significance level of 10%. Researchers used SPSS Version 25 tools. From the results of multiple linear regression analysis shows that employee performance is influenced by health and safety variables. The result of determination (R2) uses the adjusted r square value, because it uses a regression with more than one independent variable, which is 0.618, which means that the health variable and work safety variable are able to explain employee performance by 61.8% while the remaining 38.2% is influenced by other variables not examined. From the calculation results of the F test and t test, it can be seen that the health variable and the occupational safety variable simultaneously affect the employee's performance and the most dominant variable is the work safety variable.